The Particle Size of Wheat Bran Dietary Fiber Influences Its Improvement Effects on Constipation - Luyao Li; Linlin Hu; Rui Chen; Ruoyan Yang; Lingxiao Gong; Jing Wang (Foods)
Wheat bran dietary fiber (WBDF) is a potential functional additive to enrich products used for relieving constipation. The purpose of this study was to understand the effects of different particle size ranges (mean sizes of 84.14, 61.74, 37.39, and 22.33 μm) of WBDF on constipation. With the decrease in particle size, its morphology exhibited an increase in fiber fragmentation, larger pore sizes, and the formation of structural faults. The oil-holding capacity (OHC) and swelling capacity (SC) of WBDF were found to change with particle size, with the highest OHC observed at 37.39 μm and the greatest SC at 84.14 μm. Animal experiments demonstrated that the WBDF of smaller particle sizes significantly alleviated loperamide-induced constipation with an increased intestinal propulsion rate, decreased first melanin excretion time, and reduced gastric residual rate. Meanwhile, WBDF samples markedly increased serum MTL and serum AChE levels. Notably, compared with the constipation model (CMNC) group, the small intestinal propulsion rate in the MPS40 group increased by 41.21%, and the gastric residue rate significantly decreased by 19.69%. The improvement in constipation symptoms was most pronounced. Additionally, the abundance of Lactobacillus in the MPS40 group increased by 52.52%, while the relative abundance of Prevotella decreased by 83.55%, and the diversity of the gut microbiota was altered. These findings provide valuable insights into the potential commercial applications of WBDF in fiber-enriched functional foods to support intestinal health.